Discovery of anti-Ebola virus multi-target inhibitors from traditional Chinese medicine database using molecular screening, biophysical investigation, and binding free energy calculations - Abbas Khan; Abrar Mohammad Sayaf; Anwar Mohammad; Fahad M. Alshabrmi; Tarek Benameur; Dong-Qing Wei; Kar Kheng Yeoh; Abdelali Agouni (Journal of Infection and Public Health)
Introduction: Ebola virus (EBOV) is a highly lethal RNA virus that causes severe hemorrhagic fever in humans and non-human primates. The lack of effective treatment or vaccine for this pathogen poses a serious threat to a global pandemic. Therefore, it is imperative to explore new drugs and therapies to combat this life-threatening infection. Materials and methods: In this study, we employed in silico methods to assess the inhibitory activity of natural products from traditional Chinese medicine (TCM) against four EBOV proteins that are crucial for viral replication and assembly: VP40, VP35, VP30, and VP24. We performed molecular docking of TCM compounds with the EBOV proteins and screened them based on their docking scores, binding free energies, and pharmacokinetic properties. Results: Our results pinpointed eight TCM compounds (TCM1797, TCM2872, TCM250, TCM2837, TCM2644, TCM4697, TCM2322, and TCM277) that exhibited superior efficacy in inhibiting all the EBOV proteins compared to the controls. These compounds interacted with key residues of the EBOV proteins through various types of bonds, such as hydrogen bonds, salt bridges, and π-π interactions, forming stable complexes that could disrupt the function of the EBOV proteins. These compounds were found to possess known antiviral activity, acceptable pharmacokinetic properties, and human usage history, which make them promising candidates for anti-EBOV drug development. Moreover, the molecular simulation analysis confirmed the binding stability, structural compactness, and residue flexibility properties of these compounds. Furthermore, the binding free energy results revealed that VP30-TCM2644, VP30-TCM4697, VP35-TCM2837, VP24-TCM250, and VP24-TCM277 complexes exhibit significant binding free energy values compared to the control ligands. Principal Component Analysis (PCA) and Free Energy Landscape (FEL) results revealed the trajectories' motion and conformational energy states. Conclusions: Our findings provide valuable insights into the molecular mechanisms driving the efficacy of TCM drugs against EBOV and suggest novel approaches for the development of anti-EBOV therapies.